Medicinal plants used for dermatological disorders among the Nyamwezi community in Tabora region, Tanzania - Kacholi, David Sylvester (Ethnobotany Research and Applications, 2024)
Background: Dermatological disorders (DDs) are a significant public health concern worldwide as they are considerably affecting the quality of human health and problematic to cure due to persistence. This study aimed to census the traditional medicinal plants (TMPs) used to treat DDs in the Tabora region, Tanzania. Methods: Semi-structured interviews were conducted to collect information from traditional healers (THs). The emphasis was on local plant names, cured DDs, plant parts used, preparation, and administration of remedies. Quantitative approaches, including family importance value (FIV), species use value (SUV), plant part value (PPV), Jaccard index of similarity (JI), and informant consensus factor (ICF), were calculated too. Results: Sixty-four TMPs from 32 families were recorded for treating 14 DDs. The dominant family and life form were Fabaceae (with 20.3% of all TMPs and FIV of 3.455) and tree (50%), respectively. The preferred mode of utilisation and route of administration were crushing (28.1%) and topical (67.2%), respectively, while leaf (PPV = 2.86) was the most utilised plant part. The TMP with the highest SUV (0.818) was Bidens Pilosa L. (Asteraceae). A significant number of TMPs (42.2%) were used for wound healing. The highest ICF was recorded for ringworms (0.972) and the least for sores (0.924). The maximum similarity (JI = 8.3) was with the study from South Africa. Conclusion: The study exposed the significance of TMPs used by the THs of the Tabora region against DDs. To offer an understanding of each plant’s anti-infective role, an investigation to authenticate the therapeutic potential of the recorded TMPs is underway. This study suggests a need to create awareness among locals and other stakeholders for conserving TMPs and indigenous knowledge in the region and the country at large. Keywords: Skin disorders, ethnomedicine, medicinal plants, quantitative indices, traditional knowledge, wound healing